Behind Many Visages: The Waluku Cultivating Civilization Tour as Part of the Visitor Flow Management Program in the Borobudur District - Silviyani, Asna (Gadjah Mada Journal of Tourism Studies, 2024)
The Borobudur Temple is a vulnerable cultural heritage site confronting the challenge of overcrowding impacting site preservation, visitor experience, and economic viability. This study analyzed the extension of visitor flow management applications to the buffer zone in heritage locations, focusing on the enhancement of the trip experience. The Waluku: Cultivating Civilization sub-theme, integral to the Borobudur Trail of Civilization concept, has the ability to enhance preservation via the Visitor Flow Management Process, which encompasses three phases: restricted, redistributive, and interpretative. This research employed qualitative methods by gathering data through interviews, literature reviews, and observations. The research findings revealed that the three stages operate independently and do not significantly affect the preservation of the Borobudur Temple's physical and cultural assets. Restrictions could undermine the objective of enhancing engagement and interaction with culture and nature, rendering them less effective. Meanwhile, the other two stages had minimal impact due to infrequent reservations. Itineraries may vary based on demand, and there is no interpretative narrative concerning the relationship between relief and tourism activities. Conflicts of interest and insufficient local community engagement provide barriers to the program's development.